Antiviral Activity of Pistacia atlantica subsp. Kurdica Extract Against Herpes Simplex Virus Type 1 - Shahin Gavanji; Hojjat Baghshahi; Azizollah Bakhtari; Ali Mohamadi; Zahra Hamami Chamgordani; Mojtaba Khandan; Javaher Sinaei (Gazi Medical Journal)
Objective: Most research on the therapeutic effects of wild pistachio species has focused on bacteria and fungi. This study investigated the flavonoid and phenolic contents of different leaves and hulls of Pistacia atlantica(P. atlantica) subsp. Kurdica (P. atlantica subsp. Kurdica) extracts and their effect on herpes simplex virus 1 (HSV1). Methods: In this study, aqueous, ethanolic, and methanolic extracts of the leaf and hull of P. atlantica subsp. Kurdica were prepared by the percolation method. The total phenolic and flavonoid contents in different extracts were measured by UV/Vis spectrophotometry using the Folin-Ciocâlteu reagent and the colorimetric method of aluminum chloride, respectively. On African green monkey kidney cells (VERO), the ethanolic extract of P. atlantica subsp. Kurdica was tested for toxicity. Furthermore, 50% cytotoxic and inhibitory concentrations (CC50 and IC50) were identified. Results: Compared with aqueous and methanolic extracts, the ethanolic extract of the leaf and hull of P. atlantica subsp. Kurdica had the highest phenolic and flavonoid concentrations. In addition, our study showed that CC50 values were 661.81 and 795.21 μg/mL. Also, IC50 values were 97.51 and 110.82 μg/mL for leaf and hull extracts, respectively. The selectivity index for the ethanolic leaf and hull extracts were 6.79 and 7.18, respectively. Conclusion: Our results showed that P. atlantica subsp. Kurdica had an anti-HSV1 effect in a dose-dependent manner but at a higher dose than acyclovir. Ethanolic extract of P. atlantica subsp. Kurdica is probably a suitable herbal medicine with anti-herpetic effects.